2013
DOI: 10.1007/s00431-013-2097-1
|View full text |Cite
|
Sign up to set email alerts
|

Celiac crisis presenting with status epilepticus and encephalopathy

Abstract: We report herein on the first case of celiac crisis presenting with status epilepticus and encephalopathy in the absence of profound GI symptoms. Our case suggests that celiac crisis should be considered in the differential of seizures and encephalopathy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…3 Celiac crisis presenting with status epilepticus and encephalopathy in the absence of profound GI symptom has been recently described. 4 A meta-analysis of the few evidence-based data available on these disorders in children showed that the relative risk of epilepsy in individuals with CD, and of CD in individuals with epilepsy, compared with the general population, was 2.1 and 1.7, respectively. In the vast majority of these patients, wakefulness EEGs revealed focal abnormalities, mainly localized in one or both occipital regions.…”
Section: Introductionmentioning
confidence: 99%
“…3 Celiac crisis presenting with status epilepticus and encephalopathy in the absence of profound GI symptom has been recently described. 4 A meta-analysis of the few evidence-based data available on these disorders in children showed that the relative risk of epilepsy in individuals with CD, and of CD in individuals with epilepsy, compared with the general population, was 2.1 and 1.7, respectively. In the vast majority of these patients, wakefulness EEGs revealed focal abnormalities, mainly localized in one or both occipital regions.…”
Section: Introductionmentioning
confidence: 99%
“…In the child reported here, recurrent episodes of GBS occurred several months before the development of classic gastrointestinal signs and symptoms of CD, thus highlighting the possibility that neurologic manifestations may precede gastrointestinal CD manifestations in children as well as adults. This observation has been reported in pediatric patients with headache [ 8 , 9 ], opsoclonus-myoclonus [ 10 ], recurrent optic neuritis [ 11 ], recurrent acute encephalopathy [ 12 ], status epilepticus [ 13 , 14 ], recurrent transient hemiplegia [ 15 ], cerebral venous sinus thrombosis [ 16 ], and transverse myelitis [ 17 ].…”
Section: Discussionmentioning
confidence: 60%
“…5 Neurologic symptoms as first manifestation of CD in children are even more unusual than complications. 11 Nevertheless, several pediatric cases of CD 11 -18 (all confirmed with biopsy except for 1 patient due to young age 16 ), with varying neurologic presentations have been described, such as headaches, 12 opsoclonus-myoclonus, 13 recurrent optic neuritis in the context of psoriasis and partial IgA and IgG3 deficiency, 14 recurrent acute encephalopathy, 11 status epilepticus/encephalopathy, 15 peripheral neuropathy, 17 recurrent transient hemiplegia with infarction of the brain, 18 and 2 children with cerebral venous sinus thrombosis. 16 A GFD alone 12,17 or combined with other treatments 11,13,15,16,18 led to improvement 13,18 or even complete resolution 11, 12, 15 -17 of the various neurologic symptoms in these pediatric CD cases.…”
Section: Discussionmentioning
confidence: 99%